2014
DOI: 10.1371/journal.pone.0087848
|View full text |Cite
|
Sign up to set email alerts
|

KDT501, a Derivative from Hops, Normalizes Glucose Metabolism and Body Weight in Rodent Models of Diabetes

Abstract: Aims/HypothesisWe developed KDT501, a novel substituted 1,3-cyclopentadione chemically derived from hop extracts, and evaluated it in various in vitro and in vivo models of diabetes and insulin sensitivity.MethodsKDT501 was evaluated for anti-inflammatory effects in monocyte/macrophage cells; agonistic activity for peroxisome proliferator-activated receptors (PPAR); lipogenesis and gene expression profile in human subcutaneous adipocytes. Body composition, glucose, insulin sensitivity, and lipids were assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 37 publications
0
37
0
Order By: Relevance
“…In examining the influence of isohumulones on obesity, Konda et al reported that a specific molecule synthesized from the isohumulone THIAA mixture had the ability to improve insulin signaling and obesity in both the diet-induced obesity mouse model of type 2 diabetes and the Zucker diabetic fatty rat model [49]. This study demonstrated that the isohumulone pharmacophore represents itself as a privileged structure that influences adipocyte physiology and adiposity.…”
Section: Influence Of the Hops-derived Isohumulones On Obesitymentioning
confidence: 84%
“…In examining the influence of isohumulones on obesity, Konda et al reported that a specific molecule synthesized from the isohumulone THIAA mixture had the ability to improve insulin signaling and obesity in both the diet-induced obesity mouse model of type 2 diabetes and the Zucker diabetic fatty rat model [49]. This study demonstrated that the isohumulone pharmacophore represents itself as a privileged structure that influences adipocyte physiology and adiposity.…”
Section: Influence Of the Hops-derived Isohumulones On Obesitymentioning
confidence: 84%
“…Interestingly, KDT501 administration dose-dependently reduced weight gain in ZDF rats, while pioglitazone gained the weight. In addition, KDT501 reduced total cholesterol unlike pioglitazone, suggesting that the anti-diabetic action of KDT501 differs from that of pioglitazone (Konda et al, 2014). This study suggests that KDT501 might be a novel therapeutic agent for the management of T2DM.…”
Section: ) Falcarindiolmentioning
confidence: 79%
“…Administration of KDT501 in the DIO mouse and the ZDF rat improved glucose metabolism and reduced plasma HbA1c while it dose-dependently reduced the weight gain in the ZDF rat (Konda et al, 2014). Amorfrutin B…”
Section: Mbx-102mentioning
confidence: 99%
See 2 more Smart Citations